2018
DOI: 10.3390/children5080106
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of the Timely Initiation of Complementary Feeding among Children Aged 6–23 Months in Rupandehi District, Nepal

Abstract: Although the predictors of the timely initiation of complementary feeding are well-known elsewhere, there is less awareness of the topic in Nepal. The current study was undertaken to identify the correlates of timely initiation of complementary feeding among children aged 6–23 months. A community-based cross-sectional study was conducted in the Rupandehi district, Nepal. A total of 155 mother-child pairs were selected using a simple random sampling technique. Logistic regression with adjustment for potential c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 27 publications
6
6
0
Order By: Relevance
“…In this study we found that maternal education significantly correlated with early initiation of breastfeeding in line with other studies [ 10 , 36 , 41 43 ]. Hence educated women have the ability to understand the benefits of early initiation of breastfeeding and provision of colostrum to their newborns provided by health care workers as well as have better accessibility to attend ANC and have better media exposure.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study we found that maternal education significantly correlated with early initiation of breastfeeding in line with other studies [ 10 , 36 , 41 43 ]. Hence educated women have the ability to understand the benefits of early initiation of breastfeeding and provision of colostrum to their newborns provided by health care workers as well as have better accessibility to attend ANC and have better media exposure.…”
Section: Discussionsupporting
confidence: 93%
“…The practice of EIBF enables further provision of immunoglobulin and other vital bioactive molecule-rich colostrum for newborns that are critical for their immunity, growth and development [ 4 , 9 ]. In addition, EIBF practice encourages bonding between child and mother resulting in legitimate outcome for infant and child development [ 10 12 ]. Further, EIBF practice has an implication for both short and long-term benefit for mothers in the case of reducing postpartum haemorrhage, lower risk of obesity in post-delivery, advance in birth spacing period, as well as reduces the risk of breast and ovarian cancer in the long run [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Male children were more likely to have had timely initiation of complementary feeding. A similar finding was reported from a study conducted in other parts of Nepal [ 44 ] which reflects the long-standing traditional gender norm that discriminates against timely feeding of a female child [ 45 ].…”
Section: Discussionsupporting
confidence: 87%
“…Studies conducted in China and Sweden found no association between the two [69,70], whereas others [71,72] reported primiparous mothers were more likely to adopt EBF, which highlights the importance of educating multiparous women. Furthermore, as has been reported previously [51,73], we found CF feeding at six months was more common for male babies, which may reflect the long-standing traditional gender norm that discriminates against female child feeding [51].…”
Section: Discussionsupporting
confidence: 80%